Pendampingan Pelaksanaan Proyek Penguatan Profil Pelajar Pancasila (P5) Tema Bangunlah Jiwa dan Raganya di SMA KORPRI Banjarmasin - Rizkiana, Fitria; Prasiska, Emilda; Apriani, Herlina; Wardhani, Raden Roro Ariessanty Alicia Kusuma (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
It must be realized that communication is one way for humans to convey ideas and collaborate. Every individual must have the courage and skill to speak, including students who are studying at school. Students who are not skilled at speaking will have difficulty working with other students. In fact, many activities at school require this skill, such as in discussions, meetings, presentations and so on. Students who are less skilled at speaking tend not to be confident in conveying their ideas or thoughts. Indirectly, this will also hinder students from achieving, both in academic and non-academic fields. This community service activity was carried out at SMA KORPRI Banjarmasin with a target of 20 students. The activity lasted for ± 3 months with a total of 5 meetings. Based on the results of the community service activities that have been carried out, it is known that most students can feel the benefits of the mentoring that has been given and can increase their self-confidence and public speaking skills.